2016
DOI: 10.1007/s40279-016-0555-4
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Correlates of Sedentary Behavior in Adolescents: Systematic Review and Meta-Analysis

Abstract: BackgroundThe body of evidence on associations between socioeconomic status (SES) and sedentary behaviors in adolescents is growing.ObjectivesThe overall aims of our study were to conduct a systematic review and meta-analysis of this evidence and to assess whether (1) the associations between SES and sedentary behavior are consistent in adolescents from low-middle-income and from high-income countries, (2) the associations vary by domain of sedentary behavior, and (3) the associations vary by SES measure.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
3
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 53 publications
6
98
3
8
Order By: Relevance
“…Our study adds to the limited knowledge about the association between high‐quality school‐level SES indicators and adolescents' fruit intake, vegetable intake, and MVPA . Furthermore, it appears, from a systematic review of SES correlates of sedentary behavior in adolescents, that our study is the first to use any kind of school‐level measure of SES …”
Section: Discussionmentioning
confidence: 88%
“…Our study adds to the limited knowledge about the association between high‐quality school‐level SES indicators and adolescents' fruit intake, vegetable intake, and MVPA . Furthermore, it appears, from a systematic review of SES correlates of sedentary behavior in adolescents, that our study is the first to use any kind of school‐level measure of SES …”
Section: Discussionmentioning
confidence: 88%
“…A faixa etária jovem é a mais ativa, em especial indivíduos com idade entre 18 e 24 anos) conforme apontado em outros estudos 9,11,12 . Nesta faixa de idade cerca de metade dos adultos jovens são ativos, declinando progressivamente, atingindo as menores frequências entre idosos.…”
Section: Discussionunclassified
“…De Craemer et al 2018reported that a higher socioeconomic status was associated with less time spent on screen-based activities in children with maternal education seemingly, the most influential parent characteristic in relation to children's sedentary activities. Another study showed that in low-to-middle income countries, sedentary behaviour, is more strongly associated with income, than with parental education (Mielke et al 2017). In the case of the present finding, it may be that more affluent parents were better able to provide less sedentary pursuits for their preschool children such as paying for physical activity sessions (e.g.…”
Section: Parent and Home Characteristics And Who Guidelinesmentioning
confidence: 99%